PENDIDIKAN LINGKUNGAN BUDAYA JAKARTA UNTUK MENINGKATKAN KETERAMPILAN LITERASI BUDAYA PESERTA DIDIK DI SEKOLAH DASAR NEGERI PONDOK BAMBU 02 - Savira, Sheren Virgia; Dewi, Ratna Sari; Jamaludin, Ujang (STKIP Persada Khatulistiwa Sintang, 2026)
This study aimed to describe the implementation of the local content subject PLBJ (Pendidikan Lingkungan dan Budaya Jakarta) in improving students’ cultural literacy skills at SD Negeri Pondok Bambu 02, East Jakarta. The research employed a descriptive qualitative approach, with data collected through interviews, observations, and documentation involving the principal, third- and sixth-grade teachers, and students from both grades. The findings revealed that PLBJ learning was designed in a contextual and interactive manner by integrating Betawi cultural values into activities such as traditional dance, songs, and handicraft making. These activities contributed to the enhancement of cultural literacy in terms of understanding, expression, and appreciative attitudes. In conclusion, PLBJ plays an important role in fostering students’ cultural literacy skills at the elementary school level.